IMPROVING STUDENTS’ SPEAKING ABILITY THROUGH PRAISE QUESTION POLISH (PQP) METHOD AT THE X AK 1 SMK NEGERI 1 ANGKOLA TIMUR - Abdul Rahman Siagian (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2017)
The objective of this research was to describe about how to improve students’ speaking ability through Praise Question Polish (PQP) method at the X AK 1 students of SMK Negeri 1 Angkola Timur. Action research method was the research method that used by the writer to conduct this research. Subject of this research was the X AK 1 students of SMK Negeri 1 Angkola Timur, namely 34 students. Next, the writer limits this method in two cycles. Therefore, this research runs in cycle 1 and cycle 2. Next, the writer took many kinds of techniques for collecting data, namely observation, field note, test, and documentation. Therefore, the writer used observation check list, sheet of field note, sheet of test, and photos’ document. To analysis data, the writer used qualitative analysis based on the Hubermen’s model. For this case, the writer should make reducation, description, and take conclusion of the data. The result of this research showed that the students got improvement. In other words, there was improvement of students’ speaking ability through Praise Question Polish (PQP) method. Whereby, the improvement could be seen from students’ result on test, exactly the improvement move from cycle 1 to cycle 2. In cycle 1 students got 71.17 and students got 76.32 in cycle 2.